Metabolic Syndrome and Psoriasis: Mechanisms and Future Directions - Hao, Yan; Zhu, Ya-juan; Zou, Song; Zhou, Pei; Hu, Ya-wen; Zhao, Qi-xiang; Gu, Lin-na; Zhang, Hao-zhou; Wang, Zhen; Li, Jiong (Frontiers in Immunology, 2021)
Psoriasis is an immune-mediated systemic disease with associated comorbidities, including metabolic syndrome (MetS) which contributes substantially to premature mortality in patients with psoriasis. However, the pathological mechanisms underlying this comorbidity are unclear. Studies have shown that the pathological parameters of psoriasis mediate the development of MetS. We reviewed the potential mechanisms which mediate the association between psoriasis and MetS, including endoplasmic reticulum stress, pro-inflammatory cytokine releases, excess production of reactive oxygen species, alterations in adipocytokine levels and gut microbiota dysbiosis. Here, we highlight important research questions regarding this association and offer insights into MetS research and treatment.